The Correlation Age and Body Mass Index (BMI) Score with Blood Pressure in Hypertension Patient - Erni Tri Indarti; Ernawati (Master of Public Health Program Universitas STRADA Indonesia, 2024)
Hypertension is a condition where the blood vessels have high blood pressure against the pressure of the artery walls when the blood is pumped by the heart throughout the body. The higher the blood pressure, the harder the heart works. The risk of hypertension with a BMI is two to three times higher than that of a normal or thin body weight. This study aims to determine the relationship between age and body mass index (BMI) score with blood pressure in hypertensive patients. Correlation research design with a cross sectional approach on 1-31 August 2023. The population of all hypertensive patients in the Seruni Room at Dolopo Hospital is 35 patients with a sample size of 35 respondents. Sampling uses Accidental Sampling. Independent variables: Age using a questionnaire and Body Mass Index (BMI) using a weight and height observation sheet and the dependent variable Blood Pressure using a Blood Pressure Observation Sheet. The results of the Pearson product moment test show that the p value for age and systolic blood pressure is 0.000 and the Pearson correlation is 0.659, so there is a strong relationship between age and systolic blood pressure in hypertensive patients. The results of the Pearson product moment test show that the p value for age and diastolic blood pressure is 0.000 and the Pearson correlation is 0.647, so there is a strong relationship between age and diastolic blood pressure in hypertensive patients. The results of the Pearson product moment test show that the p value of the BMI score with systolic blood pressure is 0.003 and the Pearson correlation is 0.483, so there is a relationship between BMI score and systolic blood pressure in hypertensive patients with a moderate relationship. the results of the Pearson product moment test show that the p value of the BMI score with diastolic blood pressure is 0.002 and the Pearson correlation is 0.513 so that there is a relationship between the BMI score and diastolic blood pressure in hypertensive patients with a moderate relationship. Obesity can cause hypertension through various mechanisms, obesity occurs due to an increase in plasma volume and cardiac output which will increase blood pressure. So it is hoped that hypertensive patients maintain their diet and activity so that their body weight is in the normal category.